Negative thermal expansion of nanoporous anodic aluminum oxide membranes - Forzani, Luisina (2019)
We have measured the thermal expansion of Ni nanowires (NWs) electrodeposited into self-organized nanoporous amorphous aluminum oxide (AAO) membranes without an Al substrate using X-ray diffraction between 110 K and 350 K. The results indicate an average thermal expansion of the Ni NWs - along the wire axis - of α ¯ NiNW = − 1.6 ± 1.5 × 10 − 6 K − 1. Assuming a bulk-like thermal expansion of the isolated Ni NWs, this result indicates that AAO also has a negative thermal expansion. We estimate the thermal expansion of nanoporous AAO to be α AAO = − 5 ± 1 × 10 − 6 K − 1. We show that data obtained previously on the thermal expansion of metallic NWs grown in the nanoporous AAO may be interpreted as originating from a negative thermal expansion of the matrix.